Ependymosarcoma presenting as recurrence in a primary left parieto-occipital ependymoma - Pallavi Prasad; Harshita Baranwal; Neelima Gupta (Indian Journal of Pathology and Microbiology)
Ependymomas are glial tumors that may arise from the supratentorial, posterior fossa, and spinal compartments. Conventional ependymomas belong to WHO grade 2. Gliosarcoma is described as a variant of IDH-wildtype glioblastoma, comprising a biphasic tissue pattern with alternating areas displaying glial and mesenchymal differentiation. It may develop in an ependymoma, in addition to astrocytomas. This sarcomatous transformation portends a more aggressive behavior; hence, this entity should be kept in mind during the management of lesions with atypical imaging features on diagnosis. We report a rare presentation of ependymosarcoma presenting nearly 1.5 years later after the excision of a conventional ependymoma in a young female. Upon presentation as recurrence, the patient developed symptoms and atypical imaging findings. Histopathological and immunohistochemical examination of the excised tumor specimens revealed sarcomatous change occurring in an operated prior conventional ependymoma.